Produktivitas dan Komposisi Hasil Tangkapan Sero Berdasarkan Fase Bulan Di Perairan Tapulaga Kecamatan Soropia Kabupaten Konawe - Kadek Lindawati; Abdullah Abdullah; Hasnia Arami; Muslim Tadjuddah; Ahmad Mustafa; Syamsul Kamri (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2022)
Guilding barrier is a type of fishing gear that is fixed and passive, which in collecting fish is very dependent on the tides. Based on this, this research was conducted to know: 1) the number of catches of sero; 2) species composition and fish size composition; and 3) sero fishery productivity based on the moon phase. The research was conducted in April-June 2022 in Tapulaga Waters, Soropia District, Konawe. Sampling was carried out in 4 lunar phases including the new moon phase, the first quarter moon, the bright moon, and the second quarter moon. Found 357 individuals caught consisting of 21 species of fish. The highest species composition was found in the second quarter with 129 individuals (36.13%), and the lowest in the quarter with 54 individuals (15.12%). The three (3) dominant fish species are squid (Loligo sp), rabbitfish  (Siganus canaliculatus), and giant trevally (Caranx ignobilis). The caught squid (Loligo sp.) occupy all size ranges from the smallest (10.3-15.4 cmTL) to the largest (46.6-51.8 cmTL) in each lunar phase, except for the new moon phase. Caranxignobilis ranges from 13.3-38.1 cmTL, with the highest size composition at 16.9-20.5 cmTL in the first quarter moon phase. Siganus canaliculatus caught at sizes 3.3-19.8 cmTL had the highest catches at sizes 3.3-4.4, namely the new moon, full moon, and second quarter moon phases. The lunar phase has a significant effect on the number of individuals caught where the new moon phase and the second quarter lunar phase have the highest productivity, namely an average of  3 kg.